2002
DOI: 10.1046/j.1460-2695.2002.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

R‐curve behaviour of friction stir welds in aluminium‐lithium alloy 2195

Abstract: The fracture resistance of friction stir welds in 2195‐T8 is described in this paper. R‐curves were produced for several crack planes, parallel to the welding direction and situated at varying distances from the weld centreline. The friction stir weld was also characterized by hardness and tensile testing. Fracture resistance of the friction stir weld is compared to the base metal and to a variable polarity plasma arc weld. Results show that the material in and around the friction stir weld is tougher than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Since the yield strength of the transversely loaded FSW specimens are less than the yield strength of the base metal, the base metal experienced predominantly elastic strain throughout the test [5]. The mechanical properties for all the welded specimens where lower than the base material, as is the case for other precipitation hardened aluminum alloys [30]. Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 88%
See 1 more Smart Citation
“…Since the yield strength of the transversely loaded FSW specimens are less than the yield strength of the base metal, the base metal experienced predominantly elastic strain throughout the test [5]. The mechanical properties for all the welded specimens where lower than the base material, as is the case for other precipitation hardened aluminum alloys [30]. Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 88%
“…For example, Li et al and Oertelt et al [28,29] reported that in 2195 the strengthening precipitates like T1 were no longer present in the weld nugget. The T1 is considered to be the primary strengthening precipitate in the 2195 alloy [30]. Away from the weld nugget, hardness levels increased with increasing distance as precipitation hardening became more effective.…”
Section: Weld Microstructure and Hardnessmentioning
confidence: 99%
“…In any case it seems that friction stir welds behave better than those obtained by fusion welding methods. Fracture toughness of FSW welds has been measured both as significantly higher than that of the base metal (Kroninger & Reynolds, 2002;Mishra & Ma, 2005) and as lower than the base metal (Derry & Robson, 2008). In the first case, this happens both in nugget zone and in HAZ/TMAZ region, even if in this latter case the values are lower than in the nugget.…”
Section: A Simple Approach To the Study Of The Ageing Behaviour Of Lamentioning
confidence: 93%
“…The FSW consists of: a nugget, or stirred zone, a thermo‐mechanical affected zone (TMAZ) and a heat affected zone (HAZ). The modified microstructure resulting from FSW is asymmetric about the weld centreline 2 . This is due to the advancing and retreating sides of the weld corresponding to maximum and minimum relative velocities between the tool and work‐piece 3 …”
Section: Introductionmentioning
confidence: 99%